Assessment of Remote Sensing and Geoprocessing Use for Water Resources Monitoring of Granulite Dome and River Basin from Eastern Ghats, India - Ch. Ramakrishna; Ch. Muralikrishna; D. Mallikarjuna Rao; Vaikunta Rao Lakinani; Satyanarayana Yalakala (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
The aim of this work is to portray the Madhurawada dome and Gosthani river basin with about 400 sq km located North of Visakhapatnam city more precisely close to the sea of Bay of Bengal. The study was done using the IRS-IB imagery and the field survey conducted for various structural elements and geological, litho logical data. The treatment and classification of the imaginary data were synchronized with the structural element data and geological material data. For comprehensive structural analysis and microscopic scale synoptic projection diagrams for each of the fabric elements like \(π\)S0, \(π\)S1, \(π\)S2, L1, L2, L3, have prepared separately from the domal area and river basin area. The synopsis of fabric geometry have synchronized with the lineament frequencies obtained from the remote sensing imagery. The concentrated sets of lineament frequency trends are distinctly recognized along the zones of quartzites and sheared khondalite plains. Curvilinear lineament fabric is often used to indicate the principal axial orientations of prominent domal fold patterns, showing doubly plunging recumbent fold systems. For the monitoring of groundwater resource zones, intersecting lineament patterns and their synchronised structural structure are extremely important. The river basin regulated by structural controls were expressed with cross cutting lineament pattern. For the first time the authors delineated and monitored water resources lineament frequency zones in the domal areas and paleo-channels of the river basin. The lineaments intersecting zones in the Pedi plain areas are favourable zones for large diameter dug wells. For the first time the authors delineated groundwater resource lineament frequency zones in the area.